Retinal artery and vein occlusion in calciphylaxis - Andrea Naranjo; Nadim Rayess; Emily Ryan; Michael Iv; Vinit B. Mahajan (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To report a case of branch retinal artery occlusion (BRAO) followed by branch retinal vein occlusion (BRVO) and paracentral acute middle maculopathy (PAMM) in a patient with confirmed calciphylaxis. Observations: A 52-year-old female with a history of BRAO in the right eye one-year prior presented with decreased vision and a new inferotemporal scotoma. Computed tomography angiography of the head and neck demonstrated vascular calcifications at the origin of both ophthalmic arteries, which were otherwise poorly visualized. Ophthalmic examination demonstrated retinal whitening superiorly with intraretinal hemorrhages inferiorly. Optical coherence tomography (OCT) demonstrated middle retinal hyperreflectivity and a mild epiretinal membrane. Fluorescein angiography (FFA) demonstrated delayed perfusion of superior retinal arcade. On further questioning, patient was found to have a history of IgA nephropathy with end-stage renal disease, secondary hyperparathyroidism and calciphylaxis. Calciphylaxis is a systemic disease, characterized by high levels of calcium and progressive calcification of the vascular medial layer leading to ischemia. Anterior ischemic optic neuropathy (AION) and crystalline retinopathy have been reported as ocular manifestations of calciphylaxis, however, there are very few reports on ophthalmic manifestations of calciphylaxis. Conclusion and importance: Clinical manifestations of calciphylaxis are variable and a detailed clinical history is important to suspect calciphylaxis. Calciphylaxis should be considered in the differential diagnosis of BRAO, BRVO, PAMM or any ophthalmic vascular manifestation in patients with end-stage renal disease.